Comparative Genomic Analysis of the Foodborne Pathogen Burkholderia gladioli pv. cocovenenans Harboring a Bongkrekic Acid Biosynthesis Gene Cluster - Peng, Zixin; Dottorini, Tania; Hu, Yue; Li, Menghan; Yan, Shaofei; Fanning, Séamus; Baker, Michelle; Xu, Jin; Li, Fengqin (Frontiers in Microbiology, 2021)
The environmental bacterium Burkholderia gladioli pv. cocovenenans (B. cocovenenans) has been linked to fatal food poisoning cases in Asia and Africa. Bongkrekic acid (BA), a mitochondrial toxin produced by B. cocovenenans, is thought to be responsible for these outbreaks. While there are over 80 species in the Burkholderia genus, B. cocovenenans is the only pathovar capable of producing BA and causing human death. However, the genomic features of B. gladioli and the evolution of the BA biosynthesis gene cluster, bon, in B. cocovenenans remain elusive. In this study, 239 whole genome sequences (WGSs) of B. gladioli, isolated from 12 countries collected over 100 years, were used to analyze the intra-species genomic diversity and phylogenetic relationships of B. gladioli and to explore the origin and evolution of the bon gene cluster. Our results showed that the genome-wide average nucleotide identity (ANI) values were above 97.29% for pairs of B. gladioli genomes. Thirty-six of the 239 (15.06%) B. gladioli genomes, isolated from corn, rice, fruits, soil and patients from Asia, Europe, North America and South America, contained the bon gene cluster and formed three clades within the phylogenetic tree. Pan- and core-genome analysis suggested that the BA biosynthesis genes were recently acquired. Comparative genome analysis of the bon gene cluster showed that complex recombination events contributed to this toxin biosynthesis gene cluster’s evolution and formation. This study suggests that a better understanding of the genomic diversity and evolution of this lethal foodborne pathovar will potentially contribute to B. cocovenenans food poisoning outbreak prevention.